Un ἄγραφος νόμος en el epistolario de Sinesio de Cirene - Fernández Nieto, Francisco Javier (Antigüedad y Cristianismo, 1991)
Sinesius of Gyrene’s Ep. 5 before the inminente shipwreck, mentions the laws of Adrastia. The passengers of the ship rely on the efectiveness of these laws. Such laws are no more than a singular formulation of the agraphoi nomoi in the Greek world, that are still deeply rooted in the members of the Christian community of the Pentapolis.